2012
DOI: 10.1590/s0001-37652012005000059
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of neem's oil, a potential biocide against the invasive mussel Limnoperna fortunei (Dunker 1857)

Abstract: The golden mussel Limnoperna fortunei (Dunker 1857) is one of the most distributed Nuisance Invasive Species (NIS) in South America, and a threat of great concern for the industry of the area. In this study, we carried out toxicity tests made with a Neem's oil solution with L. fortunei larvae and benthonic adults (7, 13 and 19 ± 1 mm). Tests with non-target species (Daphnia magna, Lactuca sativa and Cnesterodon decemmculatus) were also made with the aim to evaluate the potential toxicity of the Neem's solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
(15 reference statements)
0
9
0
2
Order By: Relevance
“…A new threat appeared in the region in the mid-1980s and early 1990s –the introduction of invasive bivalve species such as Corbicula fluminea (Müller, 1774) and Limnoperna fortunei (Dunker, 1857)​​ [ 31 ], [ 32 ]. Limnoperna fortunei has an aggressive impact on the environment because it is an ecosystem engineer [ 32 ]. These bioinvasions have changed the structure of communities in impacted freshwater bodies, probably causing further reduction of Unionidan species abundance [ 30 ], [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A new threat appeared in the region in the mid-1980s and early 1990s –the introduction of invasive bivalve species such as Corbicula fluminea (Müller, 1774) and Limnoperna fortunei (Dunker, 1857)​​ [ 31 ], [ 32 ]. Limnoperna fortunei has an aggressive impact on the environment because it is an ecosystem engineer [ 32 ]. These bioinvasions have changed the structure of communities in impacted freshwater bodies, probably causing further reduction of Unionidan species abundance [ 30 ], [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review identifies a lack of standardization in the procedures that are used in experimental studies of L. fortunei, such as sampling, transport, rearing, monitoring of the animal's health, acclimation time to the laboratory, size range of the tested animals, monitored physico-chemical parameters, food availability during the experiments, and criteria for the selection of suitable specimens to be tested for each bioassay (Cataldo et al, 2003;Pereyra et al, 2011Pereyra et al, , 2012Di Fiori et al, 2012;Mansur et al, 2012;Calazans et al, 2013;Montresor et al, 2013;Sylvester et al, 2013). In fact, differences between the tested procedures in experimental studies may account for some of the discrepancy observed in the literature results (Rolla and Mota, 2010;Montresor et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The NOAEC (No-Observed-Adverse-Effect-Concentration) is by definition, the highest concentration at which survival of the test organism is not significantly different from the control [30,33]. In other words, it is the highest concentration from the serial dilutions in which the number of fishes died is not significantly different from that in the control.…”
Section: Discussionmentioning
confidence: 99%
“…The range finding test was set according to the protocols defined by OECD [29] and EPA [30]. Five serial dilutions of 100, 400, 800, 1200 and 1600 mg/L aqueous extract were prepared in 10 L aged water.…”
Section: Range Finding Testmentioning
confidence: 99%